Photon budgets and the relative effects of CDOM and pigment absorptions on primary production along a coastal salinity gradient - Berezovski, Aleksandr; Hessen, Dag O.; Andersen, Tom (Frontiers in Photobiology, 2025)
The study highlights the critical role of CDOM in coastal light attenuation and its impact on primary production (PP). We investigated the spectral attenuation of light due to water, phytoplankton pigments, detritus and coloured dissolved organic matter (CDOM) along a salinity gradient in the outer Oslofjord, Norway. By examining the effects of these components across different seasons, we aimed to elucidate their relative contributions to light absorption and PP. The findings suggest that increased terrestrial CDOM inputs, driven by climate, changed atmospheric deposition and land-use changes, could significantly affect coastal ecosystems by altering light attenuation and consequently PP and potentially leading to other ecological pressures. CDOM consistently dominated light absorption across all stations and seasons, contributing 50%–80% of the total absorption of photosynthetically active radiation. The absorption by CDOM and detritus decreased with increasing salinity, while phytoplankton absorption followed a seasonal succession. PP estimates show high seasonal variability from maximums in June to minimums in November, mainly attributed to, changes in seasonal light availability and phytoplankton biomass, followed by light attenuation by CDOM and differences in quantum yields of photosystem II (PSII). Nutrient analysis showed a seasonal pattern, with the highest nitrogen concentrations in November and depletion during more productive seasons, as well as conservative mixing throughout the salinity gradient. CDOM absorption played substantial, albeit not leading, role in influencing PP estimates, derived from a bio-optical model. CDOM was the main determinant of light attenuation across most wavelegnths.